Correlates of resistance training in post-treatment breast cancer survivors - Short, C.; James, E.; Vandelanotte, C.; Courneya, K.; Duncan, M.; Rebar, Amanda; Plotnikoff, R. (Springer, 2014)
© Springer-Verlag Berlin Heidelberg 2014. Purpose To explore demographic, health, social-cognitive and behavioural correlates of resistance training among post treatment breast cancer survivors. Methods A sample of 330 post-treatment breast cancer survivors recruited from across Australia completed a mailed questionnaire. A multivariate logistical regression model was used to test associations between independent variables and meeting the resistance training guidelines. Results Less than a quarter of the participants were meeting the resistance training guidelines of at least two sessions of resistance training per week. Higher task self-efficacy for resistance training (p<0.01) and greater goal-setting behaviour (p<0.05) were identified as significant predictors of meeting the resistance training guidelines, with a one unit increase in task self-efficacy and goal setting, increasing the odds of meeting the resistance training guidelines by a factor of approximately 1.2 (odds ratio (OR) task self-efficacy=1.23, 95% confidence interval (CI)=1.05–1.43; goal-setting OR= 1.20, 95% CI=1.04–1.38). No other variables significantly predicted meeting the resistance training guidelines in the multivariate analysis. Conclusions Strategies targeting task self-efficacy and goal-setting behaviours are likely to be important intervention components in resistance training interventions for breast cancer survivors. Implications for cancer survivors The findings of this study will be useful for informing the development of evidence-based interventions aiming to promote resistance training among this group.